2022
DOI: 10.1108/bfj-05-2021-0576
|View full text |Cite
|
Sign up to set email alerts
|

Circularity of food systems: a review and research agenda

Abstract: PurposeThe purpose of this paper is to appraise and evaluate empirical research on circular economy in food systems, consolidating the existing knowledge and identifying shortcomings in this emerging body of research.Design/methodology/approachThe authors conducted a systematic literature review of 136 studies from the electronic databases Scopus and Web of Science. The authors also developed a thematic analysis and summarized the results in a framework.FindingsThe authors identified seven critical issues for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 156 publications
2
32
0
Order By: Relevance
“…These barriers are consistent with previous research by De Bernardi et al (2023) and Lugo et al (2023), who also identified barriers related to consumer behaviours, multisectoral coordination, business models, digital technologies, transition processes, infrastructures, methods, logistics, measurement, and performance systems. Stakeholders often lack awareness of the benefits of CE in food supply chains (Borrello et al, 2020), and the lack of an adequate governance structure impedes the establishment of standards and regulations for the adoption of CE practices (Kumar & van der Vorst, 2017).…”
Section: Resultssupporting
confidence: 92%
“…These barriers are consistent with previous research by De Bernardi et al (2023) and Lugo et al (2023), who also identified barriers related to consumer behaviours, multisectoral coordination, business models, digital technologies, transition processes, infrastructures, methods, logistics, measurement, and performance systems. Stakeholders often lack awareness of the benefits of CE in food supply chains (Borrello et al, 2020), and the lack of an adequate governance structure impedes the establishment of standards and regulations for the adoption of CE practices (Kumar & van der Vorst, 2017).…”
Section: Resultssupporting
confidence: 92%
“…The circular economy challenges the established economic model of linear production and consumption, proposing a system intentionally restorative of natural and social capital, where resources and materials circulate in regenerative production and consumption cycles (Blomsma & Brennan, 2017). The circular model reconceptualises waste as a resource and replaces the end-of-life notion with renewable closed-loop life cycles, therefore circular economy promotes waste management systems through the reduce, reuse and recycle concepts (De Bernardi et al, 2022). Academic discussions on the circular economy have gained traction since 2013, with a range of definitions of the concept.…”
Section: Circular Economymentioning
confidence: 99%
“…However, more recent debates have expanded this to cover more aspects, notably the 9R framework of refuse, rethink, reduce, reuse, repair, refurbish, remanufacture, repurpose, recycle, recover (Potting et al, 2017). Academic research on the circular economy from a business perspective considers the emergence of circular economy business models (Ferasso et al, 2020); supply chain management (Del Giudice et al, 2021) and food systems management (Alonso-Muñoz et al, 2022;De Bernardi et al, 2022). Considering circular economy systems relating to food, food waste offers little scope for reuse or recovery, however there is a stronger focus on reducing food waste, as food waste is biodegradable waste and reducing food waste can have environmental, economic and social impacts.…”
Section: Strategies and Practice Post-covidmentioning
confidence: 99%
“…The so‐called take‐make‐dispose paradigm in the agri‐food sector has several limitations, including environmental degradation, resource depletion, health and safety concerns, and socioeconomic impacts (Esposito et al, 2020; Falcone et al, 2022). Innovation toward circularity involves collaboration between stakeholders (Bloise, 2019), policy changes, technological advancements, changes in consumer behavior, and business models shift (De Bernardi et al, 2022). Hybridizing the prediction capabilities is the key to reaching complex sustainable goals: resource forecasting, waste reduction, supply chains and preventive maintenance optimization.…”
Section: Future Trendsmentioning
confidence: 99%